Evaluation of a dog with inflammatory mammary carcinoma using 18F‐2‐deoxy‐2‐fluoro‐d‐glucose positron emission tomography/computed tomography - Yoonhoi Koo; Taesik Yun; Yeon Chae; Dohee Lee; Mingyun Son; Dayoung Ku; Hakhyun Kim; Mhan‐Pyo Yang; Byeong‐Teck Kang (Veterinary Medicine and Science, 2022)
Abstract Inflammatory mammary carcinoma is known to be aggressive, which makes thorough evaluation of the severity of tumour infiltration and metastasis important in determining a recommended treatment course. This case report describes the use of 18F‐2‐deoxy‐2‐fluoro‐d‐glucose positron emission tomography/computed tomography for evaluating the invasiveness and metastasis of inflammatory mammary carcinoma in a dog.